Związek metafilozofii i filozofii. Próba charakterystyki - Makuła, Szymon (Folia Philosophica, 2018)
The paper discusses the relation of philosophy and meta-philosophy. With the use of Jerzy Perzanowski’s notion of characteristics of science and Jan Woleński’s meta-methodological typology, the author aims at presenting meta-philosophy as part of philosophy itself. Seen along such lines, meta-philosophy is part of methodology of philosophy which relates classical problems of epistemology to philosophy, just as philosophy of science does it for science. The author argues that the problems of meta-philosophy are in fact philosophical problems and sketches possible meta-philosophical positions analogous to the standpoints in methodology already given. Obviously, this way of presenting meta-philosophy is only one of its possible programs. Yet, the benefit of it is an already given conceptual framework taken from philosophy of science.